A Comparison of Pain Perception and Efficiency in NumBee versus Conventional Injection - D Kamal Naji; Z Juma Jafar; B Ahmed Yas (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: The pain and anxiety caused by ordinary dental syringes in children has led to the invention of needle-free injection, which can affect the attitude of young patients towards dentistry. The aim of this study is to compare the needle-free syringe (NumBee) and the conventional one in terms of anesthesia efficiency and pain perception during anesthetic injection and tooth cavity preparation. Methods: In this cross-sectional study, 30 patients aged 6-8 who had no experience of visiting a dentist and all of them needed Class I tooth restoration for their mandibular 1st permanent teeth, were selected. They received local anesthetic by NumBee for one side and a conventional dental syringe for the other in two randomized sequential dental treatments. Wong Baker Faces pain scale was used to assess pain perception during local anesthetic injection and cavity preparation. Efficiency was evaluated by reported symptoms during cavity preparation and the need for rescue anesthesia. Findings: NumBee injections induced less pain than cavity preparation for 12 out of 17 girls (p=0.019). However, when the children were anesthetized with NumBee, cavity preparation was significantly more painful than with inferior alveolar nerve block (p=0.013). Conclusion: According to the results of this study, NumBee injection was less painful than inferior dental nerve block. However, NumBee supplies less anesthesia than the inferior alveolar nerve block.